GBP5 Expression Predicted Prognosis of Immune Checkpoint Inhibitors in Small Cell Lung Cancer and Correlated with Tumor Immune Microenvironment - Tong Q; Li D; Yin Y; Cheng L; Ouyang S (Dove Medical Press, 2023)
Qin Tong,1,* Deyu Li,2,* Yan Yin,1 Lifang Cheng,3 Shuming Ouyang4 1Department of Oncology, The First Affiliated Hospital, Hengyang Medical School, University of South China, Hengyang, People's Republic of China; 2Department of Medical Oncology, Provincial Clinical College, Fujian Medical University, Fujian Provincial Hospital, Fuzhou, People's Republic of China; 3Department of Hematology, Shenzhen Samii Medical Center, Shenzhen, People's Republic of China; 4Gynecology & Obstetrics and Reproductive Medical Center, The First Affiliated Hospital, Hengyang Medical School, University of South China, Hengyang, People's Republic of China*These authors contributed equally to this workCorrespondence: Lifang Cheng; Shuming Ouyang, Email 1213264513@qq.com; 2021000019@usc.edu.cnBackground: The discovery and development of immune checkpoint inhibitors (ICIs) has significantly enhanced the arsenal of immunotherapy treatments available for cancer patients. The identification of biomarkers that are indicative of an individual's sensitivity to treatment with ICIs is useful for screening SCLC patients prior to commencement of any ICIs based immunotherapy. However, the relationship between GBP5 and the prognosis of SCLC immunotherapy is still unclear and requires further study.Methods: We downloaded two SCLC datasets, namely the George-SCLC and Jiang-SCLC cohorts. We used the TIDE algorithm to predict the efficacy of immunotherapy for SCLC patients. The QuanTIseq, MCPcounter, and EPIC algorithms are used to calculate the proportions of immune cells in SCLC patients. Additionally, we retrospectively collected 35 SCLC samples from the first affiliated hospital of the Hengyang Medical school.Results: Patients in each cohort were devided into two groups with high (GBP5-High) and low (GBP5-Low) expression of GBP5. In both cohorts, the GBP5-High population had a higher proportion of patients that responded well to immunotherapy (responders) (p < 0.05). In addition, both GBP5-High subgroups had significantly increased cytotoxicity, chemokines, antigen presenting, and TNF family related genes. We also determined that GBP5 was related to high-level infiltration of B cells, CD4+T cells, CD8+T cells and NK cells.Conclusion: In this study, we found that GBP5 has the potential to be used as a biomarker of ICIs efficacy for SCLC patients. GBP5 is related to the quantity of inflammatory molecules, a high level of immune infiltration, and a highly activated immune response pathway.Keywords: GBP5, small cell lung cancer, prognosis, tumor immune microenvironment, immune checkpoint inhibitors